2022
DOI: 10.3390/nu14245262
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat Intake among Chinese Adults and Their Relationships with Blood Lipids: Findings from China Nutrition and Health Surveillance and Comparison with the PURE Study

Abstract: Dietary fat intake in the Chinese population has increased. The PURE (prospective urban rural epidemiology) study concluded the potential advantage of total fat and saturated fats (SFA) over carbohydrates on blood lipids with the inaccurate assessment of dietary fats. We investigated the dietary fat profile among 48,315 participants (aged 30–70 years, national representative) from the China Nutrition and Health Surveillance (2015–2017), determined the relationship of various fats with blood lipid biomarkers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The protective mechanism of lipids against the risk of liver cancer might operate through the previously mentioned pathways, which requires further in-depth investigation. Additionally, dietary habits, particularly fat intake, are closely linked to lipid changes [ 77 ]. In recent years, several studies have confirmed the strong association between fat intake and the risk of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The protective mechanism of lipids against the risk of liver cancer might operate through the previously mentioned pathways, which requires further in-depth investigation. Additionally, dietary habits, particularly fat intake, are closely linked to lipid changes [ 77 ]. In recent years, several studies have confirmed the strong association between fat intake and the risk of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have shown that a low-fat diet may lower plasma TC and LDL-C levels, while a high-fat diet may lower TG [35,36]. In the China Nutrition and Health Surveillance (CNHS) (2015-2017), dietary total fat was associated with increased levels of TC, LDL-C, and HDL-C, although stronger associations were observed for dietary SFA [37]. However, we did not find significant associations between total fat and unfavorable lipid profile.…”
Section: Discussionmentioning
confidence: 99%